The Therapeutic Effects of QihaPingchuan Capsule in Combination with Triple Therapy (ICS+LABA+LAMA) on Chronic Obstructive Pulmonary Disease - Zhijun Dong
To explore the curative effect of QihaPingchuan Capsule combined with triple therapy [Inhaled Corticosteroid (ICS)+Long-Acting gb(B2 receptor Agonist (LABA)+Long-Acting Anticholinergic drug (LAMA)] on Chronic Obstructive Pulmonary Disease (COPD).s